Three new pimoid spiders from Sichuan Province, China (Araneae: Pimoidae) - Xu, Xiang; Li, Shuqiang (Zootaxa, 2009)
Three new species of pimoid spiders from Sichuan, China are described and illustrated: Pimoa lata sp. nov., Weintrauboa plana sp. nov. and W. pollex sp. nov. Detailed morphological descriptions and illustrations of all three new species are given.